Resposta das cultivares de soja CD 206 e BRS 232 à variação do espaçamento entre linhas - Tibola, Cezar (2010)
The arrangement in the field of soybean plants may contribute to increased productivity. However much of the soybean has responded differently to row spacing. This study has the objective of evaluating the effect of row spacing on yield components of soybean. The experiment was conducted in Manoel Ribas, Paraná state, located in the central 24º28'39,9'' region of the state. The experimental design was in a random blocks. As a split split-plot with four replications. Plots consisted of spacing s (15 cm, 30 cm, 40 cm e 60cm) between rows and plots of the cultivars (BRS 206 and CD 232). The agronomic evaluations were plant height (PH), stem diameter (DC) number of pods per plant (NPP), number of seeds per pod (NSV), 1000 grain weight (P100G), percentage of lodging (AC) and productivity (PROD). The analysis of variance indicated significant interaction of spacing vs. cultivate to DC, NVP, NSV, P100G and productivity. In all spaces cultivar BRS 232 was higher in the NVP and P100G, and also row spacing of 15cm promoted increase of 2.7% in productivity in relation to CD 206. The regression study showed that both CD 206 and BRS 232, when planted to reduced row spacing have a significant linear response (R2 = 1) for lodging, and inversely proportional to NPP (R2 = 0.99) and productivity (R2 = 0.96). In addition, correlation analysis indicates that the height is positively correlated with lodging (r = 0.73), and the lodging negatively affects productivity (r = -0.77). Therefore it is concluded that the cultivars responded differently to spacing. However, both experienced significant fluctuations in the final yield.